DIMSUM IKAN BANDENG DAN TEPUNG KACANG HIJAU SEBAGAI MAKANAN SELINGAN TINGGI PROTEIN DAN ZAT BESI BAGI REMAJA PUTRI - Dinda Nur Baetillah; Mona Fitria; Roro Nur Fauziyah; Maryati Dewi; Mulus Gumilar (Jurnal Gizi dan Dietetik, 2022)
Food-based intervention is an effective strategy to prevent and control the incidence of iron deficiency anemia in adolescent girls. The dimsum based on milkfish and mung bean flour is a new food product as a high iron and protein snack to increase intake for adolescent girls. This study aims to determine the effect of the formulation of milkfish and mung bean flour on the organoleptic properties, iron, and protein content of the dimsum. This experimental study used a one-factor completely randomized design, namely the formulation of milkfish and mung bean flour 90%:10% (F1), 70%:30%(F2), and 50%:50%(F3). The analysis included organoleptic testing with hedonic tests by 30 moderately trained panelists, analysis of iron content using the AAS (Atomic Absorption Spectroscopy) method, and protein content analysis using the Kjeldahl Semimicro method. The results of the hedonic test showed that the best dimsum was F1. Based on Kruskall-Wallis’s test, the formulation of milkfish and mung bean flour caused a significant effect on color, taste, texture, and overall (p<0.05). One serving (75 grams) of dimsum can meet 14.6% and 13% respectively, of the recommended dietary allowance of iron and protein for adolescent girls. Further research is needed on the acceptability of dimsum in adolescent girls and estimating the shelf life of dimsum.